The catastrophic history of you and me - Rothenberg, Jess (Dial Books, 2012)
Just before her sixteenth birthday, Brie Eagan literally dies of a broken heart when her boyfriend tells her he does not love her, and she then must go through the five stages of grief, while watching her friends and family try to cope with her death, before her faith in love is restored and she can move on to the afterlife.